Penerapan Sensor Warna Gy-31 Sebagai Alat Bantu Tuna Netra Untuk Mengenali Uang Kertas Rupiah Berbasis Arduino - Joni Eka Candra; Ade Firmanto; Burhan, Rifaatul Mahmudah (AI Society & STMIK Indonesia, 2023)
Money is a common means of buying and selling transactions in use around the world. Most human needs can be obtained by using money. Because of the huge human need for money, many irresponsible parties use it to produce and distribute counterfeit money. A blind person has difficulty in reading and distinguishes between real money and counterfeit money. Required a tool that can help blind people to solve this problem. Rupiah money have a color difference on every nominal and hidden image that will glow if irradiated with ultra violet. It can be used to read nominal and authenticity. With Arduino microcontroller that combine with GY-31 color sensor and BH1750 light sensor can be used to create tool that will help the blind people to read and distinguish real money and counterfeit money. This tool is expected blind people will be spared from fraud related to counterfeit money and miss-reading the nominal.